The effects of L-theanine supplementation on the outcomes of patients with mental disorders: a systematic review - Reza Moshfeghinia; Erfan Sanaei; Sara Mostafavi; Kasra Assadian; Ali Sanaei; Getinet Ayano (BMC Psychiatry)
Abstract Background When utilized as an adjunct with antidepressants, antipsychotics, and other psychopharmacological drugs, certain amino acids, such as L-Theanine (LT), have shown potential effectiveness in enhancing the symptomatic outcomes of patients with mental disorders. Despite this, there is a lack of previous systematic reviews examining these associations. Therefore, we conducted a systematic review of randomized controlled trials examining these relationships. Methods A comprehensive systematic review was conducted, scouring six electronic databases (PubMed, Scopus, PsycINFO, Web of Science, CINAHL Complete, and Cochrane) from their inception up to June 2023, specifically focusing on randomized controlled trials that investigated the effects of LT supplementation on the outcomes of patients with mental health disorders. The Cochrane Risk of Bias Tool for Randomized Trials was employed to assess the quality of the included studies. Results Among the 419 publications identified, 11 studies from six countries — Israel, Iran, the USA, Japan, Australia, and Italy — were included in the final analysis. These studies covered a range of mental disorders, including schizophrenia, Attention-Deficit/Hyperactivity Disorder (ADHD), Obsessive-Compulsive Disorder (OCD), Major Depressive Disorder (MDD), sleep disorders, Generalized Anxiety Disorder (GAD), and Tourette syndrome. The findings demonstrated that LT supplementation reduced psychiatric symptoms more effectively than control conditions in individuals with schizophrenia, anxiety disorders, and ADHD. Conclusions The findings from this systematic review suggest that LT supplementation significantly reduced psychiatric symptoms more effectively than control conditions in individuals with schizophrenia, anxiety disorders, and ADHD. However, further studies are essential to validate these findings, deepen the understanding of the observed effects, and explore the mechanisms underlying these associations.